Peptide-Based, Two-Fluorophore, Ratiometric Probe for Quantifying Mobile Zinc in Biological Solutions - Zhang, Daniel Y. (ACS Chem Biol, 2014)
[Image: see text] Small-molecule fluorescent sensors are versatile agents for detecting mobile zinc in biology. Capitalizing on the abundance of validated mobile zinc probes, we devised a strategy for repurposing existing intensity-based sensors for quantitative applications. Using solid-phase peptide synthesis, we conjugated a zinc-sensitive Zinpyr-1 derivative and a zinc-insensitive 7-hydroxycoumarin derivative onto opposite ends of a rigid P(9)K peptide scaffold to create HcZ9, a ratiometric fluorescent probe for mobile zinc. A plate reader-based assay using HcZ9 was developed, the accuracy of which is comparable to that of atomic absorption spectroscopy. We investigated zinc accumulation in prostatic cells and zinc levels in human seminal fluid. When normal and tumorigenic cells are bathed in zinc-enriched media, cellular mobile zinc is buffered and changes slightly, but total zinc levels increase significantly. Quantification of mobile and total zinc levels in human seminal plasma revealed that the two are positively correlated with a Pearson’s coefficient of 0.73.